Development and Implementation of a TMS320C6713-based digital audio mixingincluding effects application with Matlab live remote control - Benjamin Sellak (2018)
Subject of this thesis is the implementation of the signal chain of a generic digital mixing desk’s channel. The focus hereby lies on the simulation of the most common signal processing units of such a device with Matlab, with subsequent implementation on a TMS320C6713 DSP development kit. Control over various processing Parameters in real-time via serial interface is provided by a Windows software created with the Matlab App Designer.